Intracranial hemangiopericytoma with multiple extracranial metastases: a case report - Watcharasaksilp, Wanarak; Limpastan, Kriengsak; Norasathada, Tanya; Vaniyapong, Tanat (Biomedical Sciences and Clinical Medicine, 2023)
Meningeal hemangiopericytoma (HPC) is a rare tumor in the central nervous system. It is often reported as “Meningioma”. Unlike meningiomas, HPC has a high rate of local recurrence and distant metastasis, which may occur several years after initial treatment [1]. The purpose of this article is to report a case of parasagittal hemangiopericytoma with delayed multiple extracranial metastases and local recurrence.